DISKURSUS KONTESTASI AGAMA DAN NEGARA: Reposisi Tauhid Sosial dan Nilai-nilai Pancasila (Kajian terhadap QS. al-Kᾱfirūn dan al-Ikhlᾱs) - Nuril Fajri (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Indonesian people are currently experiencing shocks, one of the biggest causes is because of the many differences that cause problems such as blaming each other, truth claim between groups, hostility, crime, even to the belief between fellow believers of Islam that undermine the moral and aqidah of the nation's children. In this case, the QS. Al-Ikhlas and QS. Al-Kafirun contains the concept of Sufism as a cornerstone of social Tauhid teaching to bridge the truth claim between the group. The author also sees the repositioning of social Tauhid and the values of Pancasila as the philosophy of the nation. This type of research is qualitative, with libraries research and paragraph interpretation theory in finding understanding of both relationships. From the study found that the concept of the state could not be released from religion. The existence of the country is a necessity according to religion. Principles of the almighty Godhead and the concept of Tauhid contained in the QS. Al-Kafirun and QS. Al-Ikhlas binds and regulates the relations of Hablum min Allᾱh and Hablum min An-Nᾱs, including issues of plurality of people and principles of Sufism in the context of Indonesia. In the hierarchy structure of Pancasila, the almighty Godhead is the first to be the teaching of Tauhid, and by the principle of Tauhid can educate the morality of the nation and maintain the purity of Tauhid and avoid from the seasonality and unbelief in The context of the Indonesian nation that is peaceful and prosperous.